Front Cover: HT‐NbOsB: Experimental and Theoretical Investigations of a Boride Structure Type Containing Boron Chains and Isolated Boron Atoms (Eur. J. Inorg. Chem. 28/2018). Issue 28 (27th June 2018) - Forsythe, Ryland; Scheifers, Jan P.; Zhang, Yuemei; Fokwa, Boniface P. T.
Abstract : The Front Cover shows parts of the crystal structures of the two modifications of NbOsB, emphasizing the different boron substructures: a finite B4 fragment (left) and the infinite B‐chain (right). The latter belongs to a new structure type, which is described in this issue for the first time. The red lines represent an X‐ray beam that is diffracted by layers of NbOsB to produce the projected diffracted image in the background (black dots), while +ΔT indicates that the new modification is the high‐temperature form. More information can be found in theFull Paper by B. P. T. Fokwa et al. For more on the story behind the cover research, see theCover Profile .